2020
DOI: 10.1021/acscatal.0c00542
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric Platinum Overlayer to Catalyze NH3 Oxidation with High Turnover Frequency

Abstract: A pulsed cathodic arc-plasma deposition of a few-nanometer-thick Pt(111) overlayer on a 50 μm-thick Fe−Cr−Al metal foil produced a thin-film catalyst; this catalyst exhibited high activity for low-temperature NH 3 oxidation and was superior to that of a conventional powder catalyst (Pt/Al 2 O 3 ). A metal honeycomb that was fabricated using a metal foil catalyst successfully demonstrated a light-off performance at a practical gas hourly space velocity of 1.2 × 10 5 h −1 . Despite its nonporosity and small surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…To achieve maximal activity and reduce contribution from the by‐products (N 2 O, NO x ), it is necessary to establish factors governing the operation of Pt/Al 2 O 3 during ammonia oxidation. At the same time it is important to reach the highest degree of Pt usage thus reducing the cost of aftertreatment systems [9] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve maximal activity and reduce contribution from the by‐products (N 2 O, NO x ), it is necessary to establish factors governing the operation of Pt/Al 2 O 3 during ammonia oxidation. At the same time it is important to reach the highest degree of Pt usage thus reducing the cost of aftertreatment systems [9] …”
Section: Introductionmentioning
confidence: 99%
“…At the same time it is important to reach the highest degree of Pt usage thus reducing the cost of aftertreatment systems. [9] Activity and selectivity of the Pt/Al 2 O 3 catalyst are affected by Pt dispersion because of the difference in the physicochemical properties of small and large Pt particles. For example, Pt metallic particles smaller than 3 nm exhibit semiconductor and dielectric properties due to the modification of electronic structure in comparison with bulk platinum.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, we recently reported another possible approach to designing an ASC, where this method uses a nonporous metal thin film prepared via pulsed arc plasma (AP) deposition. 30 We found that the as-prepared nanometer-thick Pt overlayer structure formed on the metal foil substrate exhibited high NH 3 oxidation activity comparable or superior to that of Pt/Al 2 O 3 . Furthermore, we demonstrated a light-off performance at ≥200 °C using a monolithic honeycomb comprising the metal foils at a gas hourly space velocity (GHSV) of 1.2 × 10 5 h –1 .…”
Section: Introductionmentioning
confidence: 75%
“…The NH 3 oxidation activity of the as-prepared Ir/SUS was compared with a reference Pt/SUS, which was studied previously. 30 Figure 2 shows the temperature dependencies of the concentrations of NH 3 , N 2 , N 2 O, NO, and NO 2 in the effluent gas from these catalyst beds. Both catalysts initiated NH 3 conversion at a low temperature of ∼200 °C, which rapidly increased along with an increase in temperature up to 300 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation